Drug selection for sedation in magnetic resonance imaging - Bogari, Ahmed F.; Abafallata, Doha T.; Tumayhi, Wedad A.; Alhaddaf, Muntathir H.; Alsaadi, Maram F.; Alghamdi, Samah S.; Alrashed, Ahmed A.; Alosaimi, Rawan M.; Alqahtani, Hassan A. S.; Almalki, Saeed A.; Alaama, Jumana O. (International Journal Of Community Medicine And Public Health, 2022)
Magnetic resonance imaging (MRI) is extensively used for the diagnostic purposes. Patients who undergo MRI usually spend 30 to 45 minutes in a magnetically confined, loud environment. Therefore, in order to obtain high-quality diagnostic images, the majority of children and agitated adults need anaesthesia or sedation to remain calm and in position. The success of sedation for MRIs has typically been evaluated based on both the safety of the procedure and its efficacy. It can be challenging to keep the patient's respiration and hemodynamic steady while achieving the profound sedation level required to stop them from moving. The purpose of this research is to review the available information about drug selection for sedation in MRI. For painless diagnostic MRI, a single sedative or anaesthetic drug without analgesia is safer than a cocktail of several sedatives. Various commonly used drugs for sedation are dexmedetomidine, ketamine, chloral hydrate, midazolam, pentobarbital among others. Each drug has its own efficacy and safety profile along with certain side effects. It is critically important for the physician to choose the sedative drug appropriately. Drugs used for sedative purposes should have some definite characteristics including quick onset of action, wide therapeutic window, predictable duration among certain others. Dexmedetomidine, which preserves respiratory drive, and propofol, which has a high effectiveness and quick recovery, are currently chosen for children having an ambulatory MRI. Also, the combination of these drugs is used to sedate patients. Research in future can significantly contribute to defining elaborated criteria for selection of drugs since the available literature is scarce and limited mainly to paediatric population studies.